2023
DOI: 10.1186/s13002-022-00575-z
|View full text |Cite
|
Sign up to set email alerts
|

Edible insect biodiversity and anthropo-entomophagy practices in Kalehe and Idjwi territories, D.R. Congo

Abstract: Background Located in the Eastern Democratic Republic of Congo (South-Kivu), Kalehe and Idjwi are two relatively unexplored territories with little to no research on edible insects even though anthropo-entomophagy practice is widespread. This study therefore aimed at exploring the biodiversity, perception, consumption, availability, host plants, harvesting techniques, and processing techniques of edible insects. Methods Data were collected through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Findings in this study showed that M. subhyalinus had the highest sensory score, followed by R. differens , N. septemfasciata , R. phoenicis , L. migratoria , G. africana , I. epimethea , A. mellifera , R. ferrugineus , I. oyemensis , G. trivittata and A. domesticus had the lowest sensory score based on overall acceptability, confirming the previous studies of Ishara et al 24 , 25 , who found by a survey that R. differens , M. subhyalinus , R. phoenicis and L. migratoria were among the most appreciated edible insects in Eastern Democratic Republic of Congo. Furthermore, previous studies in Portugal 74 , United States of America 75 , 76 , Italy 77 and Belgium 78 reported that A. domesticus is overall-liked.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Findings in this study showed that M. subhyalinus had the highest sensory score, followed by R. differens , N. septemfasciata , R. phoenicis , L. migratoria , G. africana , I. epimethea , A. mellifera , R. ferrugineus , I. oyemensis , G. trivittata and A. domesticus had the lowest sensory score based on overall acceptability, confirming the previous studies of Ishara et al 24 , 25 , who found by a survey that R. differens , M. subhyalinus , R. phoenicis and L. migratoria were among the most appreciated edible insects in Eastern Democratic Republic of Congo. Furthermore, previous studies in Portugal 74 , United States of America 75 , 76 , Italy 77 and Belgium 78 reported that A. domesticus is overall-liked.…”
Section: Discussionsupporting
confidence: 89%
“…This difference would result from differences in agroecological conditions under which the species was harvested 38 , 43 . The macronutrient composition of G. africana , I. oyemensis and N. septemfasciata is in some cases superior to that of several conventional meats 23 , 50 , 51 , in addition to being tasty 25 , economic 11 , 18 , and environmentally friendly 52 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Culture, influenced by the environment, history, community structure, human endeavour, mobility, and politico-economic systems, defines the rules on what is edible and what is not. The acceptance or rejection of entomophagy is a question of culture 12,[51][52][53] . In many countries, people still view eating insects as a disgusting and primitive behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to that, educating consumers about the nutritional benefits of insects and addressing misconceptions regarding the safety and hygiene of consuming insects can positively impact their willingness and attitude toward eating insects as food (Manditsera et al., 2018). The taste and texture of insects can significantly influence consumer preference and acceptance (Ishara et al., 2023). Some people find them delicious, while others may find them unpleasant to eat.…”
Section: Consumer Willingness Preference Attitude and Acceptance To C...mentioning
confidence: 99%